ANALISIS PERAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN KUALITAS PENDIDIKAN BAHASA ARAB DI ABAD 21: Studi tentang Efektivitas Media Digital dalam Pembelajaran Bahasa Arab - Umar; Anjar Sulistyani; Waslam; Sugin; Mustaji; Sugondo; Endhi Darmadi; Jaenal Arifin; Samsia Manalu; Rizka Al Fajr; Putri Dian Khairani; Rohana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Digital transformation in the 21st century has significantly influenced the teaching and learning of foreign languages, including Arabic. This research investigates the role of digital technology in enhancing the quality of Arabic language education through a qualitative library research method. A systematic review of scientific literature, including peer-reviewed journal articles, books, reports, and digital educational documents, was conducted to examine how various forms of digital technology contribute to improving Arabic learning outcomes. The findings reveal that digital tools such as artificial intelligence, multimedia learning, mobile applications, learning management systems, and virtual communication platforms facilitate more interactive, communicative, and personalized learning environments. These technologies support the development of key Arabic language competencies, including listening, speaking, reading, and writing skills, while also fostering learner motivation, autonomy, and accessibility. However, several challenges persist, including limited digital literacy among teachers, unequal technological infrastructure, insufficient institutional support, and the need for curriculum redesign to align with technological advancements. This study offers a theoretical framework for understanding the role of digital technology in modern Arabic pedagogy and provides practical recommendations for educators, institutions, and policymakers to integrate digital tools effectively and sustainably.